Assessing the introduction of ERP in SME's using the Technology Acceptance Model (TAM) / Hardaliana Ahmad Yusof - Ahmad Yusof, Hardaliana (2005)
Small and Medium Industries had become important factors in assisting the country to become more technology based to compete in a global market nowadays. If before. Small and Medium Industries works as a rural based organization but now, those industries have significant role that contributed to the wealth and growth of the country. In making the vision of Prime Minister, Datuk Seri Abdullah Ahmad Badawi to become true, who wants those small industries to compete along with big enterprises, a systematic and standard systems that helps in managing the sources of a company to be well maximized and allocated rather than being waste to different things that did not brings any benefit to the company is suggested which are Enterprise Resource Planning (ERP). Although many ways and incentives had been enforced to those companies, there is still; many companies who did not adapt to the technology suggested. This research will discuss about the factors that affecting the behavior of human in accepting new technology by using Technology Acceptance Model (TAM). Technology Acceptance Model is one of the popular models that are being used in defining the various level of acceptance of human regarding accepting new technology offered to them. A survey will be conducted in gaining the data possible in assisting the research and will be evaluated accordingly.